The evaluation of Indonesian migrant workers empowerment program at BP3TKI Serang - Nababan, Ferdinand; Suryadi, Suryadi; Matin, Matin (Universitas Malikussaleh, 2022)
The process of developing, becoming self-reliant, self-supporting, and increasing the bargaining position of lower-class groups so that they can become a pressing force in society is known as community empowerment. If community empowerment program participants understand and can perform everything that has been presented in the empowerment program, the empowerment program can run effectively and efficiently. The empowerment program must be evaluated for the program's aims and objectives to be further developed, continued, or even discontinued. This research used the CIPP evaluation model developed by Huberman. The results found that the empowerment program provided many benefits for migrants workers from preventing them back to work as migrant workers abroad but it was also found that some of them go back to work as migrant workers as the business built as a result of the empowerment program did not run as expected.